NumPy cookbook : over 90 fascinating recipes to learn and perform mathematical, scientific, and engineering Python computations with NumPy /: over 90 fascinating recipes to learn and perform mathematical, scientific, and engineering Python computations with NumPy. (2015) - Idris, Ivan
No abstract available